An experimental verification of newton's second law - Hessel, Roberto [UNESP]; Canola, Saulo Ricardo [UNESP]; Vollet, Dimas Roberto [UNESP] (FapUNIFESP (SciELO), 2013)
We describe an experimental procedure to probe the validity of Newton's second law. The experimental arrangement allows us to accelerate a glider on an air track by means of forces that are both steady and known. We also show how to determine acceleration from average speeds calculated for successive time intervals of the motion measured by using several electronic counters connected to a single-crystal oscillator circuit. Within experimental errors, the experiments clearly show the proportionality between acceleration and force for a fixed mass and between acceleration and inverse of mass for a fixed force. © by the Sociedade Brasileira de Física.
Keywords: Average speed; Measurement of acceleration; Measurement of time interval; Newton's second law